Basic beliefs of hope: a cross-cultural comparison - Andreas M. Krafft (Frontiers in Psychology)
Based on a transdisciplinary concept of hope defined as the belief in the possibility of a wished-for good and the trust in (external) resources that could make this possibility happen, the current paper attempts to evaluate the nature and role of basic beliefs related to a broader perception of hope from people with diverse cultural backgrounds. Two empirical studies from the Hope Barometer research program performed in November 2021 (N = 1.721) and November 2023 (N = 2.064) aim to compare the levels of generally perceived hope and basic beliefs of the French and Italian populations in Switzerland. Via multivariate hierarchical regression analyses we evaluate the extent to which culturally shaped basic beliefs are distinctively connected to this perception of hope. The results back up the idea that believing in the world’s goodness, fairness, abundance, controllability, and beauty, along with a sense of luck and self-worth, can give people hope that goes beyond just focusing on their own agency and ability to reach their individual goals. Despite similar socio-economic conditions, participants representing the Italian-speaking population display higher levels of perceived hope, dispositional hope, and several basic beliefs about the world and oneself. Furthermore, in the Italian group, primal world beliefs have a stronger connection to perceived hope than in the French speaking group. With regard to psychological theories of hope, these findings imply that it would be misleading to reduce the experience of hope only to individualistic goal-oriented dimensions and to ignore other elements and sources of hope, particularly when hope is related to some broader social domains.